Numerical investigation of droplet motion and coalescence by an improved lattice Boltzmann model for phase transitions and multiphase flows - Gong, Shuai; Cheng, Ping (Computers & fluids, 2012)
► An improved LBM multiphase model is proposed. ► A new scheme for the force term is proposed. ► We compared existing force incorporation methods and adopted EDM method. ► Our proposed model can give more accurate and stable numerical results. ► A high density ratio can be handled by our proposed model. An improved model for simulation of phase transitions and single-component multiphase flows by lattice Boltzmann method is proposed and developed in this paper. It is shown that both the scheme for the interparticle interaction force term and the method of incorporating the force term are important for obtaining accurate and stable numerical results for simulations of single-component multiphase flows. A new scheme for the force term is proposed and simulation results of several non-ideal equation of state suggest that the proposed scheme can greatly improve the coexistence curves. Among several methods of incorporating the force term, the exact difference method is shown to have better accuracy and stability. Furthermore, it avoids the unphysical phenomenon of relaxation time dependence. Compared with existing models, the proposed model, consisting of the new force term scheme together with the exact different method to incorporate the force term, can give more accurate and stable numerical results in a wider temperature range with the spurious currents greatly reduced. Droplet motion and coalescence processes on surfaces with wettability gradients are numerically investigated based on the newly proposed model. The velocity field and mechanism of droplet motion are illustrated in details.